The Potential Roles of Exosomes in Chronic Obstructive Pulmonary Disease - Wang, Nan; Wang, Qin; Du, Tiantian; Gabriel, Abakundana Nsenga Ariston; Wang, Xue; Sun, Li; Li, Xiaomeng; Xu, Kanghong; Jiang, Xinquan; Zhang, Yi (Frontiers in Medicine, 2021)
Currently, chronic obstructive pulmonary disease (COPD) is one of the most common chronic lung diseases. COPD is characterized by progressive loss of lung function as a result of chronic inflammatory responses in the lungs caused by repeated exposure to harmful environmental stimuli. COPD is a persistent disease with an estimated 384 million people worldwide living with COPD. It is listed as the third leading cause of death. Exosomes contain a variety of components, such as lipids, microRNAs (miRNAs), long non-coding RNAs(lncRNAs), and proteins. They are essential mediators of intercellular communication and can regulate the biological properties of target cells. With the deepening of exosome research, it is found that exosomes are strictly related to the occurrence and development of COPD. Therefore, this review aims to highlight the unique role of immune-cell-derived exosomes in disease through complex interactions and their potentials as potential biomarkers for the diagnosis and treatment of new types of COPD.